Rise Of Intraocular Pressure After Nd: YAG Laser Capsulotomy - Asma Shams; Narain Das; Jai Kumar; Beenish Khan; M. Nasir Bhatti; Anas Bin Tariq; Adnan Anwar (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2021)
Objective: Posterior capsule opacification (PCO) after cataract is a common complication of extra capsular cataract extraction with or without intraocular lens implantation. Aim of this study was to evaluate changes in intraocular pressure after Nd-Yag laser posterior capsulotomy for PCO.